The role of social capital for the development of women's enterprises: A case study of MSMEs in Padang City - Elsa Widia; Sri Mona Octafia (Optimum: Jurnal Ekonomi dan Pembangunan, 2023)
Dominantly, women's SMEs in the city of Padang claim to experience capital problems. But basically, capital is not only related to financial issues but also social issues, including social capital. In general, research tends to focus on the overall performance of MSMEs without specific studies on social capital and women. This research aims to analyze the role of social capital resources in women-owned MSMEs in Padang City using qualitative analysis methods such as Descriptive Crosstabs and Binary Logistic Regression Analysis. The social capital variables raised are the level of trust, norms or customs, mutual help and participation of MSMEs in every activity. Data will be collected through questionnaires, interviews and observations in all districts in the city of Padang. The research results reveal that social capital is considered to be able to build strong networks and has the potential to improve the performance of women-owned MSMEs in Padang City. Through surveys and interviews, this research can conclude that the variables of mutual help/cooperation and trust have been proven to be able to build their business relationships, which ultimately affect their productivity.